2020
DOI: 10.2196/18816
|View full text |Cite
|
Sign up to set email alerts
|

The Online Health Information Needs of Family Physicians: Systematic Review of Qualitative and Quantitative Studies

Abstract: Background Digitalization and the increasing availability of online information have changed the way in which information is searched for and retrieved by the public and by health professionals. The technical developments in the last two decades have transformed the methods of information retrieval. Although systematic evidence exists on the general information needs of specialists, and in particular, family physicians (FPs), there have been no recent systematic reviews to specifically address the … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 62 publications
1
23
0
Order By: Relevance
“…To identify items of relevance, such as for inclusion in various tools [ 4 - 8 ] meant to aid in assessing such technologies that are to be provided to the respective target groups (eg, physicians or other health care personnel), it is important to identify certain key aspects in the hope that these fulfill the information needs and information-seeking behaviors of users [ 55 ]. Many authors use rather detailed approaches and criteria to enable this information-seeking and more easily assess the quality of health-related apps, and they often target specific (professional) user groups [ 54 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To identify items of relevance, such as for inclusion in various tools [ 4 - 8 ] meant to aid in assessing such technologies that are to be provided to the respective target groups (eg, physicians or other health care personnel), it is important to identify certain key aspects in the hope that these fulfill the information needs and information-seeking behaviors of users [ 55 ]. Many authors use rather detailed approaches and criteria to enable this information-seeking and more easily assess the quality of health-related apps, and they often target specific (professional) user groups [ 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…For both previous studies [ 18 , 19 ], there was no clear pathway for prioritization of the principles should the need arise, apart from resource efficiency consistently being the least popular quality principle, with ensuing lesser relevance. However, in today’s medical world, time is a valuable commodity, and in fact, a lack of time or too much effort being required to adequately assess all relevant aspects is often mentioned as a barrier both to accessing information [ 55 ] as well as to employing apps in specific situations (eg, for consultations [ 57 ]). Although health apps may initially give the impression of being able to save time and reduce effort, professional ethics (eg, [ 58 , 59 ]) demand that those working in medical professions must ensure that any (digital) tools they use are up to the expected professional standards.…”
Section: Discussionmentioning
confidence: 99%
“…On the one hand, guidelines often insufficiently communicate ES or MCID to the very same physicians who should apply them or deviate from them in an evidence-based way [ 9 ]. Even if ES or MCID would be presented in guidelines, German physicians themselves identify a “lack of EBM skills” as barrier to seek for and evaluate information in the first place [ 45 ]. If an ES or MCID is neither sufficiently reported, nor comprehensibly presented to the physician, nor appropriately understood by physicians, it remains doubtful if it can be explained to the patient in the shared-decision making process.…”
Section: Discussionmentioning
confidence: 99%
“…guidelines, German physicians themselves identify a "lack of EBM skills" as barrier to seek for and evaluate information in the first place [45]. If an ES or MCID is neither sufficiently reported, nor comprehensibly presented to the physician, nor appropriately understood by physicians, it remains doubtful if it can be explained to the patient in the shared-decision making process.…”
Section: Plos Onementioning
confidence: 99%
“…The use of EBM has barriers such as lack of digital skills, low access to online information, lack of time, the science-practice gap [ 6 ], and lack of competencies among health personnel [ 7 , 8 ]. Accordingly, previous studies in Peru [ 9–11 ] and other countries [ 12–15 ] have found that physicians and medical students often have conceptual and procedural shortcomings regarding EBM competencies.…”
Section: Introductionmentioning
confidence: 99%